The Use Malays-Sambas Expressions in Developing Character Education in Sambas Primary Madrasah in Millennial Era - Putra, Purniadi; Kartika MR, Galuh Nashrulloh; Hafiz, Abdul; Pratama, Dendi; Samad, Abdul (SCAD Independent, 2021)
The Malays-Sambas expression is believed to have contributed to the Islamic basic education through an emphasis on a culture of shame expression that reflects the honor, reputation, and self-esteem of foreign cultures. The purpose of this study was to analyze the expression of Malay Sambas in improving the character education of Islamic primary students. The naturalistic phenomenological method was used to analyze the data of 6 students, 3 principals, and classroom teachers through in-depth interview sessions. The voices of participants with homogeneous characteristics of the Sambas Malay ethnicity were recorded and analyzed looking at the characteristics and implications, among others: 1) Exploration of the Sambas Malay; Suppan said,